Nvmina magna : Roma e il culto dei Grandi dei di Samotracia - Cruccas, Emiliano, (Archaeopress Roman archaeology ;, 2019)
Underlines the main aspects of the cult of the Great Gods of Samothrace in light of the influences of Roman cultural and mythological substratum.